Atividade da enzima atpase dependente de MG2+ em glândulas salivares de triatomíneos (heteroptera, triatominae) - Anhê, Ana C. B. M. [UNESP]; Azeredo-Oliveira, Maria T. V. [UNESP] (FapUNIFESP (SciELO), 2017)
Mg2+-ATPase activity was detected in the three salivary glands of adult triatomines, males and females, of Triatoma infestans (Klug, 1834) and Panstrongylus megistus (Burmeister, 1835) (Heteroptera, Triatominae). A predominance of binucleated cells in D1 and D2 and mononucleated in D3 was observed, with bulky and polyploidy nuclei. ATPase activity was detected in the nuclei, possibly in euchromatin and nucleolus, where this enzyme probably acts in the transcription process. ATPase reaction was also evidenced in the nuclear membrane, which is probably associated with nuclear-cytoplasmatic transport. These characteristics indicate a high metabolism and protein synthesis, which must be essential to saliva production as well as in maintaining the hematophagy of triatomines.
Mg2+-dependent ATpase activity in triatomine salivary glands (heteroptera, triatominae)
Keywords: Euchromatin; Gland; Nuclear membrane; Nucleolus; Phosphatase